Match activity and physiological load during a clay-court tennis tournament in elite female players - Fernandez-Fernandez, J.; Sanz-Rivas, D.; Fernandez-Garcia, B.; Mendez-Villanueva, A. (Journal of Sports Sciences, 2008)
The aim of this study was to determine the match activity and physiological demands of women's tennis during a 3-day clay-court tennis tournament. The activity profile of eight players was determined by filming each competitive match with video cameras. Metabolic-perceptual measurements-blood samples and individual ratings of perceived exertion (RPE)-were taken while the players were sitting during permitted changeover breaks in play. The activity profile of the players was as follows: strokes per rally, 2.5 ± 1.6; rally duration, 7.2 ± 5.2 s; rest time between rallies, 15.5 ± 7.3 s; effective playing time, 21.6 ± 6.1%; work-to-rest ratio, 1:2.1. Blood lactate concentration [2.2 ± 0.9 mmol/l (n = 50) vs. 2.2 ± 0.7 mmol/l (n = 48)] and RPE values [12.2 ± 2.4 (n = 57) vs. 12 ± 2.3 (n = 57)] were not significantly different (P = 0.65-0.78) between service and return games. The results highlight the importance of taking these factors (i.e. activity patterns and physiological profile) into account when planning training strategies for competitive females players. As such, tennis training regimes should be adapted to the specific demands imposed by match-play in female players on a clay-court surface.